Investigation of Phytochemical and Antioxidant Properties of Methanol Extract and Fractions of Ballota limbata (Lamiaceae) - Waheed, I. (Medknow Publications & Media Pvt Ltd, 2014)
Ballota limbata (Lamiaceae) has been used for its antispasmodic, antiulcer, diuretic, vermifuge and sedative effects in folk medicine. However, little is known about how does it work to produce these therapeutic actions. Present research investigated phytochemical components and antioxidant properties of methanol extract and different fractions of Ballota limbata. In this study, phytochemical investigation was done by performing different chemical tests. Here, antioxidant property of the extract and fractions was investigated by using 1,1-diphenyl-2-picryl hydrazyl radical scavenging activity, total antioxidant activity by the phosphomolybdenum method, linoleic acid peroxidation, ferric thiocyanate analysis and ferric-reducing antioxidant power. Methanol extract and fractions showed presence of numerous chemical principles including alkaloids, cardiac glycosides, tannins and flavonoids. The ethyl acetate fraction exhibited higher scavenging activity compared to the other fractions under investigation. This fraction displayed 84.16±1.02% 1,1-diphenyl-2-picryl hydrazyl radical inhibition at a dose of 60 μg/ml. IC(50) for 1,1-diphenyl-2-picryl hydrazylradical-scavenging activity was 13.53±0.22 μg/ml, relative to the standard, butylatedhydroxytoluene, having IC(50) of 12.33±0.88 μg/ml. Thus, Ballota limbata showed significant antioxidant activity, which may contribute in the mechanism of above pharmacological actions.